Socio-economic Factors in Estimating the Personal Water Footprint: the Case of the Pontificia Universidad Católica del Ecuador - Chafla Martínez, Pablo (2021)
The present study aims to determine the existence of correlations between the personal water footprint (HH) estimated in a volumetric way (cubic meters / person), with certain socio-economic variables such as sex, age, family income, level of education, the type and age of the dwelling and the number of people with whom they share the dwelling. With a descriptive and exploratory research methodology, a virtual survey was conducted at the end of 2019 to the entire university community of the Pontificia Universidad Católica del Ecuador (teachers, administrators and students) at the main headquarters of Quito. It was also left open the possibility that people from outside the university could fill out the survey and in this way be able to assess whether the consumption of people from the university community who had received information on sustainable water use presented any difference with those who they had not received it. It was found that there is a significant correlation between HH and some of the socioeconomic variables analysed, such as family income, sex and educational level. It is also clear from the research that HH can be used as a good aggregate indicator of water consumption that helps to become aware of unsustainable patterns of consumption, and not being used as an instrument for hydrological management and planning due to concentration and simplicity of information it presents.